2004
DOI: 10.1038/sj.jhh.1001762
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin receptor blockade in the challenging era of systolic hypertension

Abstract: Systolic blood pressure is a major cardiovascular risk factor which is often associated with arterial stiffness. Markers of arterial stiffness, such as pulse pressure and carotid-femoral pulse wave velocity, have been proved independent predictors of cardiovascular risk. Recent evidence suggests that the renin-angiotensin system is involved in the pathogenesis of systolic hypertension and arterial stiffness. Outcome trials have shown impressive cardiovascular protection by reducing systolic blood pressure (BP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 116 publications
0
6
0
Order By: Relevance
“…The co-administration of agents from different classes results in multidimensional mechanisms of action that provide complementary cardiovascular effects [1,2]. Unfortunately, the evidence from randomized clinical trials that might guide the selection of optimal combinations of antihypertensive drugs remains limited [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…The co-administration of agents from different classes results in multidimensional mechanisms of action that provide complementary cardiovascular effects [1,2]. Unfortunately, the evidence from randomized clinical trials that might guide the selection of optimal combinations of antihypertensive drugs remains limited [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…20 Angiotensin II promotes arterial stiffness by inducing fibrosis, collagen synthesis, smooth muscle cell proliferation and calcification in the arteries. 21,22 The finding that the differences in baPWV between the measured and estimated value were smaller in the high-dose valsartan group may also indicate that high-dose valsartan exerts a greater beneficial effect on arterial stiffness. These results lend support to the contention that high-dose valsartan has a direct beneficial effect on arterial stiffness, in addition to that exerted through its antihypertensive effect.…”
Section: Valsartan In Morning Hypertensionmentioning
confidence: 89%
“…Several studies suggested that physicians might not be aggressive enough in treating hypertension, particularly regarding the systolic blood pressure [20][21][22][23][24][25]. It seems that there is still some uncertainty among primary care physicians about the importance of reducing elevated blood pressure, particularly systolic, which may explain, at least in part, the poor levels of hypertension control in the population [18].…”
Section: The Issue Of Hypertension Controlmentioning
confidence: 97%